Exercise‐associated rhythm disturbances in poorly performing Thoroughbreds: risk factors and association with racing performance. (29th October 2020) - Marr, Celia M.; Franklin, Samantha; Garrod, Georgie; Wylie, Claire; Smith, Lewis; Dukes‐McEwan, Jo; Bright, Jan; Allen, Kate
Abstract: Background: Exercise‐associated cardiac rhythm disturbances are common, but there is a lack of evidence‐based criteria on which to distinguish clinically relevant rhythm disturbances from those that are not. Objectives: To describe and characterise rhythm disturbances during clinical exercise testing; to explore potential risk factors for these rhythm disturbances and to determine whether they influenced future racing. Study design: Retrospective cohort using a convenience sample. Methods: Medical records were reviewed from two clinical services to identify horses with poor performance and/or respiratory noise with both exercise endoscopy and electrocardiography results. Respiratory and ECG findings recorded by the attending clinicians were described, and for polymorphic ventricular rhythms (n = 12), a consensus team agreed the final rhythm characterisation. Several statistical models analysing risk factors were built and racing records were reviewed to compare horses with and without rhythm disturbance. Results: Of 245 racehorses, 87 (35.5%) had no ectopic/re‐entrant rhythms, 110 (44.9%) had isolated premature depolarisations during sinus rhythm and 48 (19.6%) horses had complex tachydysrrythmias. Rhythm disturbances were detected during warm‐up in 20 horses (8.2%); during gallop in 61 horses (24.9%) and during recovery in 124 horses (50.6%). Most complex rhythm events occurred during recovery, but there was one horse with a single couplet during gallop and another with a triplet during gallop. Fifteen horses (one with frequent isolated premature depolarisations and 14 complex rhythms) were considered by clinicians to be potentially contributing to poor performance. Treadmill exercise tests, the presence of exercise‐associated upper respiratory tract obstructions and National Hunt racehorses were associated with rhythm disturbances. The proportion of horses racing again after diagnosis (82%) was similar in all groups and univariable analysis revealed no significant associations between subsequent racing and the presence of any ectopic/re‐entrant rhythm, or the various sub‐groups based on phase of exercise in which this was detected. Main limitations: Reliance on retrospective data collection from medical records with no control group. Exercise ECGs were collected using only 1 or 2 leads. Variables examined as risk factors could be considered to be inter‐related and our sub‐groups were small. Conclusions: This study confirms a high prevalence of cardiac rhythm disturbances, including complex ectopic/re‐entrant rhythms, in poorly performing racehorses. Detection of rhythm disturbances may vary with exercise test conditions and exercise‐associated upper respiratory tract obstructions increase the risk of rhythm disturbances.